Search for supersymmetry in electroweak production with photons and large missing transverse energy in pp collisions at ?s = 8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
Results are reported from a search for supersymmetry with gauge-mediated supersymmetry breaking in electroweak production. Final states with photons and large missing transverse energy ( ET miss) were examined. The data sample was collected in pp collisions at ?s=8TeV with the CMS detector at the LHC and corresponds to 7.4fb-1. The analysis focuses on scenarios in which the lightest neutralino has bino- or wino-like components, resulting in decays to photons and gravitinos, where the gravitinos escape undetected. The data were obtained using a specially designed trigger with dedicated low thresholds, providing good sensitivity to signatures with photons, ET miss, and low hadronic energy. No excess of events over the standard model expectation is observed. The results are interpreted using the model of general gauge mediation. With the wino mass fixed at 10GeV above that of the bino, wino masses below 710GeV are excluded at 95% confidence level. Constraints are also set in the context of two simplified models, for which the analysis sets the lowest cross section limits on the electroweak production of supersymmetric particles. © 2016 The Author.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2016). Search for supersymmetry in electroweak production with photons and large missing transverse energy in pp collisions at ?s=8TeV. Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 759, 479-500. doi:10.1016/j.physletb.2016.05.088
Keywords: Cms; Physics; Supersymmetry